2011
DOI: 10.1002/jid.1817
|View full text |Cite
|
Sign up to set email alerts
|

Delivery Mechanisms and Impact of Microfinance Training in Indian Self‐help Groups

Abstract: We evaluate the effect of delivery mechanisms for training provided by facilitators of self‐help groups. Indian self‐help groups are unique in that they are mainly non‐government organisation–formed microfinance groups but later funded by commercial banks. We correct for both membership and training endogeneity. Training impacts assets but not income. Underlying conditions that benefit training include better infrastructure (as in paved roads), linkage model type and training organiser. Copyright © 2011 John W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 7 publications
(10 reference statements)
1
15
0
Order By: Relevance
“…They have to charge low interest rates to their clients to enable manage regular loan repayments. These findings are in line with Wenner et al (2007;Swain and Varghese (2013) and Papias & Ganesan (2009) who shared that, high interest rates charged by most microfinance institutions on credit facilities contributed to loan default and low-quality portfolio performance of the company. Despite of strong appraisal and assessment strategies, high interest rates to borrowers results to default payments and high portfolio at risk of the MFIs.…”
Section: Econometric Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…They have to charge low interest rates to their clients to enable manage regular loan repayments. These findings are in line with Wenner et al (2007;Swain and Varghese (2013) and Papias & Ganesan (2009) who shared that, high interest rates charged by most microfinance institutions on credit facilities contributed to loan default and low-quality portfolio performance of the company. Despite of strong appraisal and assessment strategies, high interest rates to borrowers results to default payments and high portfolio at risk of the MFIs.…”
Section: Econometric Resultssupporting
confidence: 86%
“…It is argued that a balance has to be reached between what clients can afford and what the lending organization needs to earn, to cover all costs involved in lending for sustainable microfinance operation. Swain and Varghese (2013); Nyamsogoro, (2010) and Kar, & Swain, (2014) advised that, financial institutions should charge higher interest rates only to credit facilities identified to have higher probability of default. As such businesses with high risk of success should attract higher interest rates.…”
Section: Related Literaturementioning
confidence: 99%
“…In the microfinance literature, recent studies acknowledge the complexity of the microfinance industry, highlighting the importance of loan officers (Kar, 2013;Sagamba, Shchetinin, & Yusupov, 2013), the local and global institutions involved in the microfinance transaction (Aitken, 2013;Boehe & Cruz, 2013;Haile, Bock, & Folmer, 2012), and the presence of other intermediaries, such as training or business development programs (Epstein & Yuthas, 2013;Sievers & Vandenberg, 2007;Swain & Varghese, 2013). Other studies revisit the premise that women are the best targets for microfinance, aiming sometimes to critique this premise, and sometimes to underscore it (D'Espallier, Guérin, & Mersland, 2011;Maclean, 2013;Moodie, 2013;Swamy, 2014) Yet, we have few clues about how the divergent motivations of stakeholders play out within microfinance organizations invested in particular gendered discourses.…”
Section: Cultural Adaptation In Global Microfinance Organizationsmentioning
confidence: 99%
“…This finding supports the results of a study conducted by the National Council of Applied Economic Research (), which found that SHG growth in North India has remained slow because of a lack of awareness, gender inequality, and lack of motivation. Swain and Varghese () also concluded that although training has a positive impact on SHG members, organizing training sessions in the villages has remained a major issue because of problems such as poor infrastructure, unavailability of local trainers, and remote location.…”
Section: Discussionmentioning
confidence: 99%